STEAM Education Advancement and Teacher Development Abroad : A Literature Review - Charoenchanakit, Nutcha; Boonyananta, Soamshine (Journal of Graduate MCU KhonKaen Campus, 2023)
This research aimed to review the literature on STEAM education advancement and teacher development abroad. By using secondary data analysis through the Google Scholar database, summarized by analytical tables and content analysis. The results showed that according to a case study of STEAM Education Advancement and Teacher Development in South Korea and the United States, there is a consistent approach such as 1) Government agencies recognize the importance of STEAM education and teacher development 2) Research and development funding support 3) Various sectors working together on the advancement of STEAM education 4) Teacher development program continuously supported teacher afterward. Research from both countries supported that STEAM education has a positive impact on students in accordance with the goals each country desired, for example: developing students' creative thinking, analytical thinking, problem solving, collaboration, improving students' motivation, and desire to pursue a career in science, etc. The results are synthesized as a model guideline for STEAM Education Advancement in Thailand with the following key points: the government sector should first and foremost recognize the importance and benefits of STEAM education and must collaborate with network partners to support teachers throughout the process. It is necessary to start with developing teachers to have a correct understanding of STEAM education by developing their knowledge, skills, and motivation. The process of developing an integrated lesson plan and its practical implementation in the classroom must result from the collaboration of teachers. In addition, the effects of STEAM education on students should also be studied. Thus, this model for STEAM education advancement should be able to lead to a positive impact on students.